PENGUATAN AKSES DAN PARTISIPASI WARGA BELAJAR MELALUI PROGRAM PENDIDIKAN KESETARAAN DI PKBM MINDA UTAMA KOTA BANDUNG - Wawan Hermawan; Iifan Auchep Venkatanathan; Andi Sukandi (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
Equivalency education is one of the nonformal education services that plays an important role in expanding educational access for individuals who are unable to complete formal education. The success of equivalency education programs is determined not only by the availability of educational access but also by learners’ participation in the learning process. This study aims to analyze the strengthening of educational access and learner participation through the equivalency education program at PKBM Minda Utama, Bandung City. The study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and document analysis involving PKBM managers, tutors, and learners. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that educational access was strengthened through flexible learning schedules, simplified administrative requirements, and continuous program socialization to the community. Learner participation was reflected in active engagement during learning activities, supported by communicative, contextual, and needs-based learning approaches. The success of the program was supported by managerial commitment, tutor competence, and increasing public awareness of the importance of education, while economic constraints, work demands, and limited facilities remained challenges. The study concludes that educational access and learner participation are interrelated dimensions that determine the success of equivalency education programs. Therefore, strengthening both dimensions should be viewed as an integrated effort to improve the effectiveness of equivalency education and support lifelong learning